Metastatic pancreatic cancer presenting as a bleeding duodenal ulcer 30 months after initial diagnosis of duodenal ulcer. Should duodenal ulcers be biopsied or followed up with repeat endoscopy? - Lim, L.-G. (2015)
Acta Gastro-Enterologica Belgica